Estudo do fresamento de madeiras em centro de usinagem CNC - Almeida, André Luiz de Macedo [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The lack of research related to wood machining processes, including the milling, as well as the increased use of this material in the industrial sector, it creates a need to increase research involving these processes, as the sector is in full technological and environmental remodeling. This paper studies the process of milling wood, presenting an analysis of the effects of cutting speed on surface quality by measuring roughness. We used a forward speed three cutting speeds, two species of wood (Pinus elliottii and Eucalyptus grandis) and two milling tools (roughing and finishing) machined by milling concordant and discordant. Each condition was repeated six times, and the measurements were performed in the opposite direction and in favor of cutting tool, generating results of the parameters Ra (average roughness) totaling 144 trials with it. These results were statistically analyzed using analysis of variance and Tukey test. Finally it was concluded that there are significant differences between the results of varying roughness when cutting speeds, milling and types of machining types tested

A carência de trabalhos referentes aos processos de usinagem em madeira, dentre eles, o fresamento, assim como o aumento do uso deste material no setor industrial, cria-se a necessidade de se aumentar as pesquisas envolvendo esses processos, pois o setor se encontra em total evolução tecnológica e remodelação socioambiental. O presente trabalho estuda o processo de fresamento de madeiras, apresentando uma análise dos efeitos da velocidade de corte sobre a qualidade superficial através da medição de rugosidade. Foram utilizadas, uma velocidade de avanço, três velocidades de corte, duas espécies de madeira (Pinus elliottii e Eucalyptus grandis) e duas ferramentas de fresar (desbaste e acabamento) usinando através de fresamento concordante e discordante. Cada condição foi repetida seis vezes, sendo as medidas realizadas no sentido contrário e a favor do corte da ferramenta, gerando resultados dos parâmetros Ra (rugosidade média) totalizando com isso 144 ensaios. Esses resultados foram analisados estatisticamente através de análise de variância e teste de Tukey. Concluiu-se por fim que há diferenças significativas entre os resultados de rugosidade quando se variam as velocidades de corte, tipos de fresas e tipos de usinagem testada
Keywords: Usinagem; Fresadoras; Aspereza de superfície; Eucalyptus grandis; Pinus elliottii; Machining